ALFABETIZA TERESINA: Do contexto de produção da política às implicações para a alfabetização dos alunos das escolas públicas municipais de Teresina (PI) - SOUSA, Aurismar Ferreira de (2024)
This dissertation, entitled Alfabetiza Teresina: from the context of policy production to the implications for the literacy of students in municipal public schools in Teresina (PI), is the result of research developed in the Postgraduate Program in Education/Masters at the Federal University of Maranhão -UFMA, in the History, Educational Policies and Human Training Line, Educational Policies and Management and Human Training Research group. Its object of study is the Literacy Policy - Project Alfabetiza Teresina for the literacy of students in the Municipal Network of Teresina - PI, considering the context of its creation in the period from 2018 to 2022. In this context, the study was developed based on the following problem question: what are the contributions of the Literacy Policy - Projeto Alfabetiza Teresina to the literacy of students in the Teresina Municipal Network? To this end, we defined the general objective of analyzing the Literacy Policy expressed in the Alfabetiza Teresina Project and its implications for the literacy process. More specifically, we sought to analyze the literacy concept of the Alfabetiza Teresina Project; identify implementation actions/strategies of the Alfabetiza Teresina Project aimed at Literacy; evaluate actions based on the preparation and execution of reading and writing projects developed on the Network; and analyze the perception of teachers about the literacy results of students in the Literacy Cycle. The Alfabetiza Teresina Project was implemented based on Ordinance No. 240/2018, established by the Municipal Department of Education of Teresina — SEMEC, focused on the Literacy Cycle, assuming a formal commitment agreed upon by the management of the Secretariat and school management. The research was developed using a qualitative approach, using the policy cycle through Performance Theory, as a methodological resource for the study of policies, formulated by Stephen Ball and his collaborators. This approach highlights the importance of considering the nuances and specificities of schools and local communities, recognizing that educational policies are not merely “implemented”, that is, successful implementation requires adapting policies to the specific context of each school and region, being a continuous cycle that involves influences, text production and practice. The research had a theoretical basis, including a bibliographical, documentary and field review in 03 (three) teaching units, 02 (two) schools with 1st and 2nd year classes and 01 (one) Municipal Center (CMEI) that serves 1st and 2nd year classes of Elementary School. It used semi-structured interviews with managers (directors and pedagogical coordinators) and literacy teachers who work in the Literacy Cycle classes, totaling 12 participants. The data obtained was subjected to a content analysis, according to Bardin (2016), considering the conditions of production of the message, the context of reception and the effects produced. To support the research, we sought theoretical support in: Gontijo (2014), Mortatti (2014); Soares (2020), Ball (2011, 2021), Mainardes (2016), among others. The results indicate that in relation to the Alfabetiza Teresina Project, it was possible to identify positive impacts on the learning of students in the Teresina Municipal Network, especially by providing a more organized and targeted structure for monitoring the literacy process. However, perceptions about the project vary among educators. While many recognize the significant advances provided by the initiative, there is also recognition of challenges that need to be overcome.